ANALISIS PENGARUH VARIASI BUSI TERHADAP GAS BUANG - Surianto Buyung (Politeknik Katolik Saint Paul Sorong, 2020)
This research was conducted to determine the effect of variations in spark plugs on exhaust gas and fuel consumption or on a 4 stroke gasoline motorbike. To find out the effect, the calculation of the value of fuel consumption (FC) and the rate of air flow (mu) is calculated, whereas the value of the air fuel ratio is obtained by using a Gas Emission Analyzer. And also the research was carried out using 3 types of spark plugs namely RESING, NGK, DENSO spark plugs. in the condition of 4 rotation variations in each spark plug that is 1400 rpm, 1600 rpm, 1800 rpm and 2000 rpm and the fuel used is only one type, namely premium (gasoline).From the results of the research that in the Resing spark plug, ngk, denso with 1400 rpm rotation AFR value is 13.80. 10.90. 10.10. Fuel volume (m³) 0.00003, usage time (seconds) 364, fuel consumption (FC) 0.222527473, and kg / hour air flow rate 0.789972527. 1,951565934. 2,205247253, and carbon monoxide (CO) 3,55. 8.77. 9.91%. At 1600 rpm the AFR value is 13.00. 10.80. 9.97, fuel volume (m³) 0.00003, usage time (seconds) 366, fuel consumption (FC) 0.221311475, and kg / hour air flow rate 1.117622951. 2,031639344. 2,20647541, and carbon monoxide (CO) 5,00. 9.18. 9.97%. At 1800 rpm the AF value is 12.30. 10.60. 10.10, fuel volume (m³) 0.00003, usage time (seconds) 331, fuel consumption (FC) 0.244712991, and kg / hour air flow rate 1,62489426. 2,346797583. 2,43978852, and carbon monoxide 6,64. 9.59. 9.97%. And at 2000 rpm the AFR value is 11.51. 10.50. 10.10, fuel volume (m³) 0.00003, usage time (seconds) 257, fuel consumption (FC) 0.315175097, and kg / hour air flow rate 2.581284047. 3,151750973. 3,1517550973, and carbon monoxide (CO) 8,19. 10.10. 10.10%.